Selection of control algorithm parameters for a group flight of satellites - Ашуров , А. Е.; Бақыт , М. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
Selection of control algorithm parameters for a group flight of satellites